2020
DOI: 10.1080/19475705.2020.1737584
|View full text |Cite
|
Sign up to set email alerts
|

Study on overburden failure characteristics in deep thick loose seam and thick coal seam mining

Abstract: In order to solve the related problems of roof collapse in deep thick loose seam, taking the actual geological conditions of 1302 working face of Zhaolou Coal Mine as the geological background. A mechanical calculation and analysis model for a deep thick loose seam is established. A mining dynamic simulation was carried out using the numerical simulation software FLAC3D. Fracture development height was observed using a multi-stage plugging and leak detection system. Sublevel solid compaction filling technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…On‐site monitoring often relies on microseismic monitoring systems, drilling holes, and other means with which to achieve the goal of mine safety; research into gas‐bearing coal samples 13‐14 and has also involved use of acoustic emission 15 and Hopkinson pressure bar experimental systems 16 ; floor stress 17 ; and displacement 18 are also used as laboratory‐test‐based monitoring methods. To quantify cracking, some studies into crack density 19,20 and fractal dimensions 21,22 have been conducted. Scholars have successively proposed O‐shaped circle theory, 23,24 double‐circle theory, 25 the theory of the elliptic paraboloid zone, 26 etc.…”
Section: Introductionmentioning
confidence: 99%
“…On‐site monitoring often relies on microseismic monitoring systems, drilling holes, and other means with which to achieve the goal of mine safety; research into gas‐bearing coal samples 13‐14 and has also involved use of acoustic emission 15 and Hopkinson pressure bar experimental systems 16 ; floor stress 17 ; and displacement 18 are also used as laboratory‐test‐based monitoring methods. To quantify cracking, some studies into crack density 19,20 and fractal dimensions 21,22 have been conducted. Scholars have successively proposed O‐shaped circle theory, 23,24 double‐circle theory, 25 the theory of the elliptic paraboloid zone, 26 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars at home and abroad have conducted a lot of research on the failure height of thick coal seams. Liu et al studied overburden failure characteristics in deep thick loose seam and thick coal seam mining [4]. Wang al.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied the process of overburden failure in steeply inclined multiseam mining: insights from physical modelling [15]. Liu et al used numerical simulation software FLAC3D to investigate overburden failure characteristics in deep thick loose seam and thick coal seam mining [4]. Xu et al analyzed the overburden migration and failure characteristics after mining shallow buried coal seams with thick loose layer based on actual measurement data and simulation results [16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2020) confirmed that the transition layers of the bedrock layers and the loose layers has a support effect on mining subsidence. Liu et al (2020) found that the thick loose layer formed a bending collapse zone, fracture development zone and caving zone during the mining process through simulation analysis, and derived a prediction model based on elastic mechanics. Xu et al (2020) studied the movement laws of the overlying bedrock while mining shallow buried coal seams under thick loose layers.…”
Section: Introductionmentioning
confidence: 99%